Pendapatan daerah dan fiskal stress akibat Covid-19 di Indonesia - Juniarti, Juniarti; Noersanti, Lina; Akhmadi, Ali; Mustika, Maya; Ardheta, Preztika Ayu; Hendro, Junaidi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This research project seeks to analyze and gather evidence about regional income and whether the Covid-19 pandemic has caused fiscal stress in all provinces of Indonesia. The data used includes the budgets for all provinces in Indonesia for 2018 and 2019 prior to the pandemic, and for 2020 and 2021 during the pandemic, with a total of 34 provinces included in the study. The sampling method utilized was saturated sampling, while data processing was done through the Wilcoxon Signed Ranks Test with SPSS 26. The findings indicate that there were notable differences in regional income, transfers to regions, and village funds before and during the pandemic, leading to fiscal stress. This component is crucial to regional income, as it directly involves the central government, and thus the pandemic has had a significant impact on the provinces. However, there were no differences in regional original income or other income before and during the pandemic, indicating that there was no fiscal stress.